Enhancing Students’ Speaking Skill Through Drill and Practice Method - Hana Yulinda Fithriyani; Arief Zul Fauzi (International Journal of Studies in International Education, 2024)
Speaking skills are more prioritized considering the function of English, namely for communication. This encourages the development of trends in English learning to include speaking in the sub-achievements of course learning in larger portions. in order to improve students' speaking skills, drill and practice method is needed to be applied as a variation of learning methods in the classroom. This research is aimed at determining what to extent drill and practice method can  improve students' speaking skills. Subjects of the research were 36 students of Diploma III Computer Engineering Study Program. Data were collected using pre-tests and post-tests, observation and documentation. Data were analyzed quantitatively using test and qualitatively described. The findings showed that in the first cycle, 83.33% of students' speaking scores were above the KKM, then in the second cycle it increased to 97.22%. This also applies to the average student score which increased from 67.38 in cycle 1 to 73.72 in the second cycle.In conclusion, drill and practice method can enhance students’ speaking skill.